The expression of MMP-2, MMP-7, MMP-9, and TIMP-1 in chronic rhinosinusitis and nasal polyposis - Can, Ilknur Haberal; Ceylan, Kursat; Caydere, Muzaffer; Samim, Ethem Erdal; Ustun, Huseyin; Karasoy, Durdu Sertkaya (Otolaryngology-head and neck surgery, 2008)
To investigate the expression and clinical significance of MMP-2, MMP-7, MMP-9, and TIMP-1 in patients with nasal polyposis (NP) and chronic rhinosinusitis (CRS). Prospective study. This study involved 54 patients. There were three groups: nasal polyposis group, chronic rhinosinusitis group, and control group. Specimens were collected during endoscopic sinus surgery. Each sample was immunohistochemically examined. Expression of MMP-2 was found significantly increased in NP, whereas MMP-7 expression was found significantly increased in CRS (P < 0.001). TIMP-1 was significantly high in control group compared to CRS and NP (P < 0.001 and P = 0.002, respectively). Different regulation type of activation of MMPs has been found in these two diseases. If MMP-2 expression is intense in the mucosa, then this ends with polyp formation; if MMP-7 expression is intense, it ends with CRS or stays as CRS.